Direct Selling dalam Usaha Perasuransian Perspektif Hukum Islam - Seri Utami Ningsih, SH. - (Al - Muamalat: Jurnal Hukum dan Ekonomi Syariah, 2020)
Insurance companies such as PT. Life Insurance Central Asia Raya, PT. Prudential Life Insurance, PT. Generali Indonesia Life Insurance, PT. Tugu Mandiri Life Insurance, PT. MNC Life Insurance, PT. Asuransi Jiwasraya (Persero), and PT. Sequis Life Life Insurance has marketed one of its insurance products with a direct sales system or better known as direct selling. Direct selling does not include the marketing channels stipulated in the Financial Services Authority Regulation (POJK) No. 23 of 2015 concerning Insurance Products and Marketing of Insurance Products. Based on the POJK, direct selling practiced by insurance companies is illegal. Direct selling is developed by insurance agents by recruiting insurance agents in a row. Otoritas Jasa Keuangan (OJK) confirms direct selling as the development of insurance marketing methods. Supervision is unmindful of the principle of legal certainty, professionalism, and openness. In sadd az}-z}ariah, negligent supervision of the OJK is an act that endangers health insurance. OJK must review the direct selling marketing developed by insurance agents further